The value chain of green hydrogen for fuel cell buses – A case study for the Rhine-Main area in Germany. (14th February 2020) - Coleman, D.; Kopp, M.; Wagner, T.; Scheppat, B.
Abstract: As an immanent necessity to reduce global greenhouse gas emissions, the energy transition poses a major challenge for the next 30 years, as it includes a cross-sectoral increase of fluctuating renewable energy production, grid extension to meet regional electricity supply and demand as well as an increase of energy storage capacity. Within the power-to-gas concept, hydrogen is considered as one of the most promising solutions. The paper presents a scenario-based bottom-up approach to analyse the hydrogen supply chain to substitute diesel with fuel cell buses in the Rhine-Main area in central Germany for the year 2025. The analysis is based on field data derived from the 6 MW power-to-gas plant "Energiepark Mainz" and the bus demonstration project "H2 -Bus Rhein-Main". The system is modelled to run simulations on varying demand scenarios. The outcome is minimised hydrogen production costs derived from the optimal scheduling of a power-to-gas plant in terms of the demand. The assessment includes the energy procurement for hydrogen production, different hydrogen delivery options and spatial analysis of potential power-to-gas locations. Highlights: The value chain of green hydrogen. Analysis of different market penetration scenarios for FC-buses vs BE-buses. Spatial analysis of power to gas locations in a regional context. Optimisation of the electricity purchase for minimising the H2 production costs.